The Transformational Leadership Effect on Job Satisfaction and Job Performance - Kishen Kishen; Tantri Yanuar Rahmat Syah; Syah Rina Anindita (Journal of Multidisciplinary Academic, 2020)
The purpose of this study aimed to provide an overview of the relationship between transformational leadership and job satisfaction level experienced by employees. Leadership is an organization or institution refers to the style of its leaders in providing direction, implementing plans, and motivating employees. To achieve the result, the data has been collected through by questionnaires distributed online to 120 employees working in Tangerang from various companies was used. Furthermore, the data observation was analyzed by Structural Equation Modeling (SEM) Lisrel. The results of this study showed that transformational leadership is a special leadership style that is applied by superiors that motivates their subordinates to appear at a higher level by inspiring them, offering in intellectual challenges also paying attention to their individual needs. Job satisfaction strongly refers to employee perceptions of their work environment, relationships between coworkers, income and promotion opportunities. Therefore, this study has some conclusions that employee leadership styles are likely to be influenced by several factors, including demographic characteristics. Therefore, the reciprocal relationship between organizational culture and transformational leadership in job satisfaction has been sucessful.